Food Security & Development in the Arab World - In Transition? - Khouri, Nadim (2012)
IFPRI Policy Seminar "Food Security & Development in the Arab World - In Transition?" presentation by Nadim Khouri, Deputy Executive Secretary, United Nations Economic & Social Commission for Western Asia at IFPRI on November 7, 2012.